The Role of the Church in Africa in Helping to Avert National Conflicts from Escalating into Violence - Kalanga, Derrick (Scriptura, 2025)
Since the 20th century, churches have significantly influenced national reconciliation following catastrophic events. Religious leaders, activists, theologians, and scholars have historically initiated and facilitated reconciliation efforts, including national truth and reconciliation commissions. However, there has been limited focus on proactive measures to prevent conflicts from escalating into catastrophes. Through a thematic analysis of qualitative documents, the article highlights that churches in Africa have frequently played a limited role in preventing socio-economic and political tensions from escalating into devastating crises. This article aims to evaluate the Church’s role in helping to prevent national conflicts from worsening. By integrating, analysing and interpreting findings from an extant body of literature with a view to show evidence at a meta-level, this article contributes to discourse on the Church and Peacebuilding and will serve as a useful resource for future national case studies on the role of the Church in helping to avert national conflicts from escalating into a catastrophe.